Pemanfaatan Media Sosial dalam Pengambilan Keputusan Berkelanjutan Vaksinasi Covid-19 - Dewi, Adelya Rachmatya; Heriyanto, Heriyanto (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2024)
This research motivated by the emergence of Covid-19 vaccination in 2021 as a result of the Covid pandemic phenomenon -19 which hit all countries including Indonesia. The emergence of Covid-19 vaccination has caused the need for information on Covid-19 vaccination to increase so sharply, that social media has become one of the main media used by the public to meet the need for information on Covid-19 vaccination. This research aims to determine the use of social media by students of the Indonesian Language and Literature Education Study Program, Nusantara University PGRI Kediri, East Java in making decisions about Covid-19 vaccination. The method used was a qualitative method using semi-structured interviews with fifteen (15) students from the Indonesian Language and Literature Education Study Program at the Nusantara PGRI University, Kediri, East Java as informants for data collection. The data obtained was analyzed using thematic analysis. The research results show three themes related to the use of social media in making Covid-19 Vaccination Decisions by students of the Indonesian Language and Literature Education Study Program at Nusantara University PGRI Kediri, East Java, who have very diverse information needs regarding Covid-19 vaccination information. 1) Utilization of social media as a means of fulfilling various information needs for Covid-19 vaccination. 2) The choice of social media platforms has quite a big influence on finding information and making decisions in carrying out Covid-19 vaccination. 3) In the process of fulfilling vaccination information via social media, there is an information evaluation stage that aims to obtain valid and credible Covid-19 vaccination information so that it can be used as a basis for making decisions about continuing Covid-19 vaccination.